Engineered Corynebacterium glutamicum as the Platform for the Production of Aromatic Aldehydes - Kim, Hyun-Song; Choi, Jung-A; Kim, Bu-Yeon; Ferrer, Lenny; Choi, Jung-Min; Wendisch, Volker F.; Lee, Jin-Ho (Frontiers in Bioengineering and Biotechnology, 2022)
Aromatic aldehydes, including 4-hydroxybenzaldehyde (4-HB aldehyde), protocatechuic (PC) aldehyde, and vanillin, are used as important flavors, fragrances, and pharmaceutical precursors and have several biological and therapeutic effects. Production of aromatic aldehydes in microbial hosts poses a challenge due to its rapid and endogenous reduction to alcohols. To address this hurdle, prospecting of the genome of Corynebacterium glutamicum yielded 27 candidate proteins that were used in comprehensive screening with a 4-hydroxybenzyl (4-HB) alcohol–producing strain. We identified that NCgl0324 has aromatic aldehyde reductase activity and contributed to 4-HB aldehyde reduction in vivo since the NCgl0324 deletion strain HB-Δ0324 produced 1.36 g/L of 4-HB aldehyde, that is, about 188% more than its parental strain. To demonstrate that NCgl0324 knockout can also improve production of PC aldehyde and vanillin, first, a basal MA303 strain that produces protocatechuate was engineered from 4-hydroxybenzoate-synthesizing C. glutamicum APS963, followed by deletion of NCgl0324 to generate PV-Δ0324. The PC aldehyde/alcohol or vanillin/vanillyl alcohol biosynthetic pathways, respectively, were able to be expanded from protocatechuate upon introduction of carboxylic acid reductase (CAR) and catechol O-methyltransferase encoded by a mutated comtm gene. In shake flask culture, the resulting NCgl0324 deletion strains PV-IΔ0324 and PV-IYΔ0324 were shown to produce 1.18 g/L PC aldehyde and 0.31 g/L vanillin, respectively. Thus, modulation of the identified NCgl0324 gene was shown to have the potential to boost production of valuable aromatic aldehydes and alcohols.